At-distance neurocognitive rehabilitation during COVID-19 pandemic: A first glance of patients’ perspectives about the process and an online platform - Geraldo, Andreia (2022)
Despite the use of digital communication technologies in neurocognitive rehabilitation has been widely used in face-to-face interventions, the difficulties of using ICT-based tools to provide rehabilitation services and the unfamiliarity of the neuropsychologists with internet interventions limited the use of these kinds of interventions in their clinical practices. The lockdown and mitigating measures associated with the COVID-19 pandemic, on the other hand, forced the use of at-distance and online interventions as a means to mitigate the impact of those measures on the mental health and rehabilitation processes of people with neurological disorders. Overall, little is known about the perspectives of patients with acquired neurological conditions about rehabilitation services delivered at distance. Therefore, the main goal of this study was to explore the perceptions that patients with neurological disorders have on at-distance online neurocognitive rehabilitation, namely during the COVID-19 pandemic. Sixteen patients with acquired neurological conditions attending an online neurocognitive rehabilitation program in a Portuguese rehabilitation center filled in an online questionnaire during the mandatory lockdown. The results of this study highlight the potential of delivering rehabilitation services at distance, presenting its advantages and limitations from patients’ perspectives, as well as suggestions for improving both neurorehabilitation processes and the online rehabilitation platform used.